The Entanglements of Agrarian Ethics with Agrarian Risks and Leveraging Them in Agricultural Health Safety - Bendixsen, C.G. (J Agromedicine, 2017)
Agriculture is the most dangerous occupation in the United States for both workers and bystanders. Family farms highlight an intersection of domesticity and labor. Agrarian ethics of animal husbandry, land stewardship, and kinship are often conflated and constructed to accommodate unpredictable risks (e.g., weather, financial markets). Here, the right or good agricultural practice is assessed in light of an acute event. Risks of illness and injury are often relegated to the realm of acute unpredictability and accepted as intrinsic to desirable ways of life. The following is a description of agrarian ethics and risks generated from personal experience and ethnographic inquiries in the Midwest, the Intermountain West, and Texas over the past 10 years. This paper assesses health and safety within agrarian ethics. These results and discussion lead us to an important conversation about how we can be more detailed in the use of terms like “cultural appropriateness.” It also raises the question as to what is really at stake in public health perspectives like those found in the socioecological and extended parallel process models when deployed in agricultural health and safety.